2020
DOI: 10.1177/0886260520907356
|View full text |Cite
|
Sign up to set email alerts
|

Client Retention in Community Treatment: Completer and Noncompleter Experiences of an Individualized, Needs-Based Partner Abuse Intervention Program

Abstract: There has been increased interest in the subjective experiences of participants of community Partner Abuse Intervention Programmes (PAIPs). In the context of high attrition rates, qualitative research is needed to understand the factors associated with sustained engagement and drop-out. Using a community non-mandated PAIP, the current study is a rare investigation of the experiences of both completers and non-completers. We explored i) the differences between completers' and non-completers' perceptions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Concerning motivation, results are mixed. While some studies reported that low motivation is related with dropout (e.g., Bennett et al, 2007;Pearson et al, 2020), others suggest that the stage of change was not related with intervention completion (e.g., Mach et al, 2017). Although only a few studies assessed the role of external factors on perpetrators' dropout (e.g., Gondolf & Foster, 1991;DeHart et al, 1999;Timko et al, 2015), it was found that men who paid more fees were more likely to attend more sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning motivation, results are mixed. While some studies reported that low motivation is related with dropout (e.g., Bennett et al, 2007;Pearson et al, 2020), others suggest that the stage of change was not related with intervention completion (e.g., Mach et al, 2017). Although only a few studies assessed the role of external factors on perpetrators' dropout (e.g., Gondolf & Foster, 1991;DeHart et al, 1999;Timko et al, 2015), it was found that men who paid more fees were more likely to attend more sessions.…”
Section: Introductionmentioning
confidence: 99%